An Analysis upon the Portrait of Anita Desai as an Artist: Exploring the Writing of Anita Desai (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Anita Desai is a distinguished Indo-Anglian novelist and has been popularly known as a literary genius both in India and abroad. Mrs. Desai has written in, and experimented with varieties of the genres of fiction like short story, the literature for children and review, articles and interviews which carry her own fictional interest and flavour. The present dissertation is an effort to bring forth some of the major aspects of Desai’s writing in all its essential facets. My chief endeavor has been to present a systematic study of Desai’s major themes, technical aspects.